The relationship of secondary school library use and library anxiety among UP Diliman freshmen students - Legaspi, Connie Lea C.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study investigates the relationship of secondary school library use - frequency of high school library use and reason/s for using the high school library and library anxiety, in terms of the four factors, namely: situational factors, social factors, psychological factors, and technical factors. Participants were 357 UP Diliman freshmen. Findings revealed that UP Diliman freshmen have high levels of anxiety across the three factors: situational, social and technical factors. In terms of psychological factors, students have a fair level of anxiety. In all, it was found that high level of library anxiety exists among UP Diliman freshmen.
Both ANOVA and Pearson correlation revealed that frequency of high school library use was significantly associated with the psychological factors. ANOVA and Pearson correlation revealed that reason/s for using the high school library was significantly correlated with the situational factors, social factors and technical factors. However, Stepwise regression analysis revealed that reason/s for using the high school library is a valid predictor of the level of anxiety in terms of the psychological factors.
Based on the findings, school administrators need to incorporate library instruction program in the students' curriculum, to provide them with the knowledge regarding the use of academic libraries and to enhance their library skills and prepare them for library use in college. Library anxiety maybe reduced if as early as high school, students are already exposed to libraries and are equipped with the necessary library skills to be competent with library use in college.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman -- Freshmen; Library use studies -- Philippines -- Quezon City; Library anxiety -- Philippines -- Quezon City